Bangunan RISDA, KM 7 Jalan Ampang, Karung Berkunci 11067 50990 Kuala Lumpur / Amalin Nur Fazirah Zairi ... [et al.] - Amalin Nur Fazirah, Zairi; Mohamad Ariff, Jayari; Muhammad Ashraf, Azman; Nurul Fatin Idayu, Azman (2019)
This report of final project is focus on integrating various aspect of the building industry. This was carried out in order to determine the aspect of organizational Management, technology, design property, building economic and financing, law, communications, project planning and management in the building. The objective of this report is, we are able to propose an integrated report consisting of multi-disciplinary approach for maintenance management in RISDA building. We also should able to justify the relationship of various personnel in maintenance organization and practice the wide array of skills, knowledge and application necessary for successful completion of project and teamwork. This integrated final project is covering the scope of study the detail of the RISDA Building, the organization of maintenance management in RISDA, maintenance policy and planning, building design and technology design, condition assessment of the building, maintenance strategy, legal aspect, financial aspect and problem and recommendations of the RISDA building. The aim of the report is to learn how maintenance department of RISDA building manage their work, plan their maintenance work for every facilities that being provide in their building and learn how they manage and plan their financial based on their expenditure for every years. The secondary aim is to state the problem of the building and provide the recommendation to solve the issues.